Coffee Tourism: from Home Products to Attractions - Leewellyn, Vincent; Palupi, Santi (E-Journal of Tourism; Volume 7 Number 1 (March 2020), 2020)
The development of rural destinations is currently one of the strategies to increase the level of welfare for the community. Indonesia, besides having natural resources, also has others potential resources such as culture, ethnicity, local languages, and many more. Those potentials can be further developed as rural destinations. This research reaches the exploratory stage to find out what is potential, excellence and what must be done in order to become a rural destination. A qualitative approach is used in this study with Head Village in Sukadana along with community leaders and organizational groups such as Youth Organization, KOMPEPAR (The Driving Force for Tourism), BUMDes (Village-Owned Enterprises), etc. The result of this research finds out the potential resources that already exist in Sukadana like Natural Resources (Cikondang Waterfall, Gunung Padang Site and Tea Plantation) and Human made – not originally designed to attract Tourists and also suggest the activities that will improve the attractions. The conclusion finds that the village community still need more improvement in knowledges and skills about rural destinations, and also the local government is still not realized yet for Sukadana Village potential resources to be a rural destination. Keywords: Coffee, Tourism, Attractions, Rural Destination